Body and world: existential developments in pandemic and covid-19 times - SILVA, FELIPE (Geografares, 2021)
How does the relationship between body and world help us to think about the current pandemic moment and, furthermore, what would be its existential implications, that is, how does the given situation influence our sense of life? This is our guiding question. The present article / essay is a proposal to incite other reflections or an invitation to dialogue regarding dimensions in which they cross in being and the sense of being-in-the-world. Home, body, world and time are examples of dimensions that, for at least 1 year, have been demanding a new position regarding our human values. In this way, it is intended to bring to reflection the distinction between “pandemic” and COVID-19, in the way that the first is the whole of the structural and symbolic problems evidenced by the second.